Nerve entrapments related to muscle herniation. Issue 4 (1st August 2019) - Tong, Olivia; Bieri, Phyllis; Herskovitz, Steven
Abstract: Background: Muscle herniation is a muscle protrusion through a fascial defect. It is a rarely reported cause of nerve entrapment. Methods: We present a case of superficial fibular (peroneal) neuropathy associated with a fibularis (peroneus) brevis muscle herniation and a review of the literature on nerve entrapments secondary to muscle herniation unrelated to compartment syndrome. Results: Eleven cases of nerve entrapments secondary to muscle herniation were identified. The superficial fibular nerve (SFN) was the most commonly entrapped nerve by fibularis muscle herniation. Patients presented with pain, numbness, or paresthesias, and an often tender, small palpable mass with a Tinel sign. Muscle MRI or ultrasound identified the lesion, and patients responded well to fasciotomy. Conclusions: The most commonly reported nerve entrapped by muscle herniation is the SFN secondary to fibularis muscle herniation. Characteristic clinical and imaging (MRI or ultrasound) features are diagnostic, and there is a salutary response to fasciotomy.